Continuous Operation of a Bragg Diffraction Type Electrooptic Frequency Shifter at 16 GHz with 65% Efficiency. (18th October 2012) - Hisatake, Shintaro; Hattori, Kenji; Nagatsuma, Tadao
Abstract : We demonstrate for the first time the continuous operation of a Bragg diffraction type electrooptic (EO) frequency shifter using a 16 GHz modulation signal. Because frequency shifting is based on the Bragg diffraction from an EO traveling phase grating (ETPG), this device can operate even in the millimeter-wave (>30 GHz) range or higher frequency range. The ETPG is generated based on the interaction between a modulation microwave guided by a microstrip line and a copropagating lightwave guided by a planner waveguide in a domain-engineered LiTaO3 EO crystal. In this work, the modulation power efficiency was improved by a factor of 11 compared with that of bulk devices by thinning the substrate so that the modulation electric field in the optical waveguide was enhanced. A shifting efficiency of 65% was achieved at the modulation power of 3 W.